2001
DOI: 10.1046/j.1365-2249.2001.01567.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtractive screening reveals up-regulation of NADPH oxidase expression in Crohn's disease intestinal macrophages

Abstract: Macrophages play a central role during the pathogenesis of inflammation. In normal intestinal mucosa surface expression of typical macrophage markers such as CD14, CD16, CD11b or T-cell co-stimulatory molecules such as CD80 or CD86 is low indicating anergy and low pro-inflammatory activity of these cells. During inflammatory bowel disease (IBD) the mucosa is invaded by a population of macrophages displaying these markers, secreting higher cytokine levels and representing an activated cell population. CD33(+) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 44 publications
(52 reference statements)
1
44
0
Order By: Relevance
“…21 These studies indicate that part of the treatment efficacy of drugs used in the treatment of IBD could be mediated by decreasing the production or effects of ROS. 22 Such information could contribute to future developments in anti-inflammatory therapy. However, no significant difference in colonic inflammation between p47 phoxÀ/À and WT mice in response to DSS challenge was reported, 9 indicating that gp47 phox and gp91 phox differ in their roles in intestinal acute inflammation, despite both being components of nicotinamide adenine dinucleotide phosphate oxidases.…”
Section: Discussionmentioning
confidence: 99%
“…21 These studies indicate that part of the treatment efficacy of drugs used in the treatment of IBD could be mediated by decreasing the production or effects of ROS. 22 Such information could contribute to future developments in anti-inflammatory therapy. However, no significant difference in colonic inflammation between p47 phoxÀ/À and WT mice in response to DSS challenge was reported, 9 indicating that gp47 phox and gp91 phox differ in their roles in intestinal acute inflammation, despite both being components of nicotinamide adenine dinucleotide phosphate oxidases.…”
Section: Discussionmentioning
confidence: 99%
“…1). Consequently they can contribute to the pathology associated with a number of autoimmune diseases, such as rheumatoid arthritis (2), multiple sclerosis (3), and inflammatory bowel disease (4) to mention a few. We have recently shown that macrophages activated in the presence of immune complexes secreted high levels of IL-10.…”
Section: Erk Activation Following Macrophage Fc␥r Ligation Leads To Cmentioning
confidence: 99%
“…A total of 10 7 cells were resuspended in 80 l of PBS and labeled with 20 l of immunomagnetic MicroBeads armed with CD33 Ab (isotype, mouse IgG1; clone, P67.6; Miltenyi Biotec). IMAC were purified twice with the help of type AS separation columns (Miltenyi Biotec) as described recently (14). Briefly, LPMNCs with magnetically labeled macrophages were passed through an AS separation column placed in the permanent magnet Super-MACS.…”
Section: Isolation Of Imacmentioning
confidence: 99%
“…In addition, IMAC from normal mucosa lack expression of receptors for bacterial wall products such as TLRs 2 and 4 (13). Colonic macrophages from normal mucosa also have low antibacterial toxicity and lack enzymes for oxidative burst reaction such as NADPH oxidase (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation